Acupressure PC6 Self-Care for Hyperemesis Gravidarum during the Covid-19 Pandemic - Viventius, Yoshua; Mihardja, Hasan; Djaali, Wahyuningsih (Writing Center IMERI FMUI, 2022)
Introduction: Most pregnant women (50–90%) generally experience nausea and vomiting during pregnancy, which usually subsides at 16–20 weeks of gestation. Approximately 0.5–2 percent experience severe nausea and vomiting, known as HG, which necessitates hospitalization. Since 2.000, the Ministry of Health of the Republic of Indonesia has been developing acupressure self-care, among other things, by implementing acupressure training (Teknologi Tepat Guna – TTG) for mild complaints about health workers. Objective: This review discusses several studies that demonstrated the effect of acupressure on HG, as well as the mechanism of acupressure, the points used, and treatment strategies. Method: The Google Scholar and PubMed databases were searched for studies published between 2010 and 2020 on how acupressure affects HG using the keywords acupressure, hyperemesis gravidarum, and PC6 point. Randomized clinical trials on human subjects and studies that measured nausea vomiting index in pregnant woman as outcomes were included. Studies that did not include clinical effects of acupressure were excluded. Results: The following studies on HG (n=4) were discovered. These studies suggested that acupressure might be considered to reduce symptoms of nausea and vomiting in pregnant women. Conclusion: Acupressure at PC6 may reduce nausea and vomiting in pregnant women by influencing gastrointestinal function via nerve stimulation to inhibit cerebral cortex function. Self-care acupressure at the PC6 point may be a therapeutic option to reduce HG during the Covid-19 pandemic.